Prevention and Recovery of COVID-19 Patients With Kampo Medicine: Review of Case Reports and Ongoing Clinical Trials - Takayama, Shin; Namiki, Takao; Odaguchi, Hiroshi; Arita, Ryutaro; Hisanaga, Akito; Mitani, Kazuo; Ito, Takashi (Frontiers in Pharmacology, 2021)
Coronavirus disease 2019 (COVID-19) spread to Japan in 2020, where the number of infected patients exceeded 250,000 and COVID-related deaths exceeded 3,500 in one year. Basic guidelines for infection control were implemented in Japan, and research and development of effective drugs and vaccines were promoted. This included considering Kampo medicine, which has a long history of treating recurring emerging viral infections. Considering the characteristics of the disease (inflammation of the upper and lower respiratory tract as well as potential neural damage and vasculitis), Kampo medicine could be considered as a treatment strategy due to its antiviral and anti-inflammatory effects induced by multiple active substances that could aid in disease prevention and recovery. In this study, case reports on the management of COVID-19 with Kampo medicine, which were published until March 31, 2021, were reviewed. The search strategy involved the use of Medline and hand-searching. Twenty two patients were treated using Kampo medicines with or without Western medicine, based on individual conditions. On the other hand, the effects of Kampo medicines as a potential preventive treatment (pre-infection), active treatment (especially in the acute and subacute stage), or treatment of sequelae to aid recovery (after infection) in the different stages of COVID-19 are being studied as research projects in the Japan Society for Oriental Medicine (JSOM). JSOM has also organized a pioneering project of clinical trials for COVID-19, some of which are now in progress.